2019
DOI: 10.21815/jde.019.124
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Levels of Dental Faculty and Students: A Survey Study at an Academic Dental Institution in Chile

Abstract: A successful health care provider may be described as a clinician capable of establishing a comprehensive diagnosis including identifying related risk factors. However, an equally important quality a clinician should possess is the ability to understand the experiences and feelings of others to allow better communication for better outcomes. It is likely that faculty empathy levels influence students' ability to demonstrate this attribute. The aim of this study was to assess the levels of empathy of dental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 53 publications
4
25
0
4
Order By: Relevance
“…Besides, Ameh et al 7 were unable to detect a significant difference in empathy between preclinical and clinical years in dental school. Our results were supported by findings of Carvajal et al 18 , who reported that clinical education improves the empathy levels of students with increased knowledge and patient interaction when compared to preclinical classes. We considered that the intention to serve patients might have created a high responsibility and motivation for the fourth-grade students.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, Ameh et al 7 were unable to detect a significant difference in empathy between preclinical and clinical years in dental school. Our results were supported by findings of Carvajal et al 18 , who reported that clinical education improves the empathy levels of students with increased knowledge and patient interaction when compared to preclinical classes. We considered that the intention to serve patients might have created a high responsibility and motivation for the fourth-grade students.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, more emphasis should be given to the role of clinical supervisors as empathetic models for students. 13 Carvajal et al 18 reported that faculty staff had higher levels of empathy when compared to students and raised a question whether their empathic behaviors would enhance the empathy levels of students. For this reason, postgraduate students were included to the present cohort, as their empathic behaviors could be important to understand the transition from studentship to professional academic life.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of medical students, the empathy score in students was significantly associated with faculty's rating of clinical competence and communication scores of students [ 27 , 30 ]. Hence, there is a greater emphasis on empathy among dental students which is evident from the recent surge in the literature on dental education [ 18 – 20 , 25 , 31 ]. In our study, a vast majority of participants believed in the importance of empathy in effective communication with patients and improved provider-patient relationship.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, a single “significant” change could be interpreted as a success, even though that change may not be that successful. Given that the concept of empathy is complex, the construction of cutoff points becomes important as a quantitative structure that makes it possible to quantify the magnitude of change in these levels and, furthermore, to have certain points of reference to credit the real meaning and true impact of an intervention to raise empathy levels 3,6,8,10,35–37 …”
Section: Discussionmentioning
confidence: 99%